Alternative stable equilibria and critical thresholds created by fire regimes and plant responses in a fire‐prone community. Issue 1 (10th August 2018) - Miller, Adam D.; Thompson, Jonathan R.; Tepley, Alan J.; Anderson‐Teixeira, Kristina J.
Abstract : Wildfire is a dominant disturbance in many ecosystems, and fire frequency and intensity are being altered as climates change. Through effects on mortality and regeneration, fire affects plant community composition, species richness, and carbon cycling. In some regions, changes to fire regimes could result in critical, non‐reversible transitions from forest to non‐forested states. For example, the Klamath ecoregion (northwest United States) supports extensive conifer forests that are initially replaced by hardwood chaparral following high‐severity fire, but eventually return to conifer forest during the fire‐free periods. Climate change alters both the fire regime and post‐fire recovery dynamics, potentially causing shrubland to persist as a stable (i.e. self‐renewing) vegetation stage, rather than an ephemeral stage. Here, we present a theoretical investigation of how changes in plant traits and fire regimes can alter the stability of communities in forest‐shrub systems such as the Klamath. Our model captures the key characteristics of the system, including life‐stage‐specific responses to disturbance and asymmetrical competitive interactions. We assess vegetation stability via invasion analysis, and conclude that portions of the landscape that are currently forested also can be stable as shrubland. We identify parameter thresholds where community equilibria change from stable to unstable, and show how these thresholds may shift in response to changes in life‐history or environmental parameters. For instance, conifer maturation rates are expected to decrease as aridity increases under climate change, and our model shows that this reduction decreases the fire frequencies at which forests become unstable. Increases in fire activity sufficient to destabilize forest communities are likely to occur in more arid future climates. If widespread, this would result in reduced carbon stocks and a positive feedback to climate change. Changes in stability may be altered by management practices.